2022
DOI: 10.1155/2022/9914931
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Fetal Congenital Cardiac and Vascular Disorders Associated with Sertraline Treatment during Pregnancy: Analysis of FAERS Data

Abstract: Objective. Sertraline is one of the most commonly used antidepressants worldwide and is one of the first-choice treatments for depression during pregnancy. This study is aimed at testing the possible association between sertraline intrauterine exposure and congenital cardiac and vascular disorder occurrences by assessing the publicly available US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods. Disproportionality analysis and Bayesian analysis were used to mine FAERS for suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Besides inhibiting the activity of PI3K, LY-294002 increases the expression of DUSP6, a dual specificity phosphatase that dephosphorylates members of the PI3K pathway. The approved antidepressant drug sertraline was reported to induce cardiac and vascular birth defects based on analysis of FAERS [58]. The ReproTox KG subnetwork of cliques/cycles suggests that such adverse birth defects could be mediated via the activation of the dehydrocholesterol reductase DHCR7 and DHCR24.…”
Section: Resultsmentioning
confidence: 99%
“…Besides inhibiting the activity of PI3K, LY-294002 increases the expression of DUSP6, a dual specificity phosphatase that dephosphorylates members of the PI3K pathway. The approved antidepressant drug sertraline was reported to induce cardiac and vascular birth defects based on analysis of FAERS [58]. The ReproTox KG subnetwork of cliques/cycles suggests that such adverse birth defects could be mediated via the activation of the dehydrocholesterol reductase DHCR7 and DHCR24.…”
Section: Resultsmentioning
confidence: 99%
“…Given the potential risks to the mother and baby, antidepressants are indicated as a first-line treatment for pregnant women with severe depression ( 15 ), whereas non-pharmacological interventions are suitable for mild to moderate cases ( 16 ). Deciding when to start, switch, or stop antidepressants during pregnancy requires careful weighing of the maternal and infant risks related to treatment and the risks related to the illness itself ( 17 ). It is mandatory to compare unfavorable outcomes after intrauterine exposure to antidepressants with those that affect the offspring of women with untreated depression, both to differentiate disease and treatment effects and to provide clinically useful information about the management of women with depression ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of antidepressants during pregnancy is a subject of debate as evidence of adverse fetal and infant outcomes remains inconclusive ( 19 ). Studies have found an association between the use of antidepressants by pregnant women and an increased risk of cardiovascular malformation ( 17 , 20 , 21 ), persistent pulmonary hypertension ( 21 , 22 ), premature birth, low birth weight ( 23 27 ) and an increased risk of psychiatric disorders in offspring, including mood disorders, TEA ( 28 ), and ADHD ( 29 , 30 ). There is, to date, a consensus in previous systematic reviews that the increased risk of premature birth and low birth weight is associated with exposure to antidepressants ( 27 ); however, the impact of the antidepressants use in the increased risk of congenital anomalies and miscarriage is unclear ( 15 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, we can mention duloxetine, which can lead to an increase in the number of abortions [ 15 ], and selective serotonin reuptake inhibitors, which increase the risk of congenital heart diseases, neonatal maladaptive syndrome, or persistent pulmonary hypertension. This is because serotonin is essential for developing all embryonic cells and organogenesis [ 14 , 16 - 18 ]. In view of the above, we consider that allopathic drugs can harm embryonic and fetal development.…”
Section: Introductionmentioning
confidence: 99%